Peranan Pesantren/Ma’had Aly Makkah dalam Meningkatkan Religiusitas Masyarakat Senggrong Andong Boyolali - Ainul Haris (STAI Ali bin Abi Thalib Surabaya, 2019)
The focus and purpose of this study is to determine the role of Aly Makkah Islamic Boarding School Senggrong Andong Boyolali in improving the religiosity of surrounding communities, and to find out the factors that support and hinder the activities of enhancing the religiosity of communities around Aly Makkah Islamic Boarding School Senggrong Andong Boyolali. This research method is descriptive qualitative with type of field research. This study found that the Aly Makkah Islamic Boarding School played an active role in improving the religiosity of the community with various religious activities. For instance, establishing a TPA (Al-Qur’an Learning Center), organizing a tabligh akbar, the Islamic study group after Maghrib prayer, Ramadan activities, the distribution of qurban meat, congregational prayers and Friday prayer. Some supporting factors to improve community religiosity are human resources (HR) who are energetic and play an active role in activities held by the Islamic Boarding School, adequate facilities and infrastructure, and social factors. While the inhibiting factors of Aly Makkah Islamic Boarding School in improving community religiosity include, lack of public awareness, lack of effectiveness of learning in TPA, and differences in understanding.